2015
DOI: 10.1007/s12032-014-0461-2
|View full text |Cite
|
Sign up to set email alerts
|

SOX5 promotes epithelial–mesenchymal transition and cell invasion via regulation of Twist1 in hepatocellular carcinoma

Abstract: The transcription factor sex determining region Y-box protein 5 (SOX5) plays important roles in various types of cancers. However, the expression and function of SOX5 in hepatocellular carcinoma (HCC) have not been elucidated. Here, we found that SOX5 is significantly up-regulated in HCC tissues and cell lines. Gain- and loss-of-function studies demonstrated that SOX5 promoted HCC cell migration and invasion. In addition, we revealed that SOX5 is linked to epithelial-mesenchymal transition (EMT) by regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
1
34
1
Order By: Relevance
“…In search of EMT markers that could be more specifically modulated by NK cells, we reevaluated the proteomic data and noticed that MeDeBO cells exposed to either NK cells or cytokines showed upregulation of SOX5, a transcription factor involved in the negative regulation of MITF and in the induction of EMT (see Supplementary Table S1; refs. 38,39). We analyzed this molecule in the melanoma lesions and found a clear statistical correlation between the rich NK-cell infiltrate and the high expression of SOX5 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In search of EMT markers that could be more specifically modulated by NK cells, we reevaluated the proteomic data and noticed that MeDeBO cells exposed to either NK cells or cytokines showed upregulation of SOX5, a transcription factor involved in the negative regulation of MITF and in the induction of EMT (see Supplementary Table S1; refs. 38,39). We analyzed this molecule in the melanoma lesions and found a clear statistical correlation between the rich NK-cell infiltrate and the high expression of SOX5 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports have demonstrated that EMT promotes cancer development via migration and invasion (24); SOX5, in addition to SOX9, has been reported to regulate EMT (25,26). To determine whether SOX6 suppressed the migration and invasion of U2OS cells via EMT regulation, markers of EMT were detected following the overexpression or downregulation of SOX6 in U2OS cells.…”
Section: Sox6 Suppresses Emt Of Os Cells Via the Regulation Of Twist1mentioning
confidence: 99%
“…SOX5 functions as transcription factors and primarily plays important roles in the regulation of embryonic development, cell fate, and chondrogenesis13. Elevated SOX5 transcripts have been related to invasive growth and reduced apoptosis in tumors and have been associated with progression of certain cancers141516. Recent studies have suggested the involvement of SOX5 in B-cell development9 and Th17 differentiation17, suggesting a role of SOX5 in immune responses.…”
mentioning
confidence: 99%